Evaluasi Program Kampung Iklim (PROKLIM) Kelurahan Margo Mulyo, Kecamatan Balikpapan Barat - Shaqnasia, Exana; Mustofa, Umar; Kadri, Mohtana Kharisma; Syafitri, Elin Diyah (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2024)
The Climate Village Program is one of the strategies of the Ministry of Environment and Forestry (KLHK) to reduce the impact of climate change. One of the areas experiencing the impact of landslide climate change is Margo Mulyo Village. The climate village program in Margo Mulyo Village aims to increase environmental resilience and reduce the risk of disasters related to climate change and can increase awareness in dealing with the impacts of climate change. The aim of this research is to evaluate the climate village program (PROKLIM) in Margo Mulyo Village. The variables that will be used in this research are effectiveness, efficiency, adequacy, alignment, responsiveness and accuracy. The sampling technique in this research was using the Slovin formula and a sample of 83 respondents was obtained. This research uses descriptive statistical analysis and a Likert scale. The results of this research showed that 3 priority variables still need improvement, but other variables also need to be improved as well.